The determinants of trade integration: an assessment of the East African Community - Kaminchia, Sheila Mwendwa (2019)
The East African Community (EAC) aims to integrate member countries through enhanced regional trade, economic policy harmonisation and coordinated investment in infrastructure. This thesis assesses the effectiveness of EAC trade policies in integrating member countries by way of lowering total bilateral trade costs. The thesis estimates and analyses total bilateral trade costs for 16 manufacturing industries over the period 1990-2012. The estimates are derived from data on production and bilateral trade flows for a sample comprising 5 EAC countries and 87 of their trade partners. The thesis then analyses the effect of two key EAC policies aimed at lowering international trade costs - the removal of intra-EAC import tariffs and the upgrading of transit roads. Chapter 2 presents the estimated total bilateral trade costs and shows the importance of natural and policy-related factors in determining the total bilateral trade costs. Chapter 3 shows that total bilateral trade costs for intra-EAC trade declined by 30 per cent after the EAC customs union protocol was implemented, and that associated non-tariff policy measures explain more of the decline in the trade costs than does the removal of import tariffs. Chapter 4 shows that the upgrading of the transit roads in the region over the period 2004-2010 lowered total bilateral trade costs by 21 per cent. This negative association is found to be stronger for industries for which trade barriers other than import tariffs are particularly important. The findings imply that upgrading the remaining Corridor roads may lower total bilateral trade costs by a further 24 per cent. This confirms that poor roads are an exigent obstacle to trade in the EAC. Overall, the thesis concludes that the observed decline in total bilateral trade costs for the EAC manufacturing sector over the study period is mainly reflective of policy actions to remove non-tariff barriers to trade and upgrade transit roads.